ANALYSIS OF SKIN CONDITIONS IN EARLY ADULT CONSUMERS USING A SKIN ANALYZER: : IMPLICATIONS FOR COSMETIC PRODUCT FORMULATION - Suryaneta, Suryaneta; Yasir, Angga Saputra; Muhtar, Wafiq Azizah; Sholeha, Aida Febina; Ambarita, Petrus Alvin Peter; Noviantoro, Tri (Indonesian Journal of Cosmetics, 2024)
This study aimed to analyze the skin characteristics of early adult consumers using data collected from a skin analyzer and explore the implications for cosmetic product formulation. The research sample consisted of 73 participants, with the majority aged between 17 and 20 years. The measured skin parameters included moisture, pores, melanin, acne (acne), wrinkles, and sensitivity. Data were analyzed using descriptive statistics and consumer segmentation techniques. The findings revealed that the early adult consumers in the sample generally exhibited low skin moisture levels (56.2%), enlarged skin pores (mean of 3.90 out of 5), fair skin pigmentation (69.9% with a melanin value of 1), severe acne severity (56.2% with an acne value of 5), minimal wrinkling (53.4% with a wrinkle value of 1), and high skin sensitivity (38.4% with a sensitivity value of 5). Based on consumer segmentation, formulation recommendations were provided for groups with dry and sensitive skin, severe acne and enlarged pores, and normal-to-oily skin with minimal wrinkle concerns. These findings highlight the need for targeted cosmetic formulations to address the specific skin concerns faced by early adult consumers. Although limitations such as a relatively small sample size and a focus on objective measurements existed, this study provides valuable insights for data-driven cosmetic product development. Further studies are recommended to investigate lifestyle and environmental factors, incorporate subjective data, and explore inter-group differences within the early adult consumer population. This research demonstrates the importance of evidence-based skin data analysis in informing cosmetic formulation strategies. By understanding and catering to the unique needs of early adult consumers, the cosmetic industry can develop more effective and satisfying products, driving market growth within this critical consumer demographic. A data-driven approach to cosmetic product development will become increasingly crucial in adapting to evolving consumer needs and preferences.